If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7(w + -1) = 28 Reorder the terms: 7(-1 + w) = 28 (-1 * 7 + w * 7) = 28 (-7 + 7w) = 28 Solving -7 + 7w = 28 Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '7' to each side of the equation. -7 + 7 + 7w = 28 + 7 Combine like terms: -7 + 7 = 0 0 + 7w = 28 + 7 7w = 28 + 7 Combine like terms: 28 + 7 = 35 7w = 35 Divide each side by '7'. w = 5 Simplifying w = 5
| (5u-7)/(4u-12) | | 2(n-2)=20 | | 15=5h+5 | | -2z-5=-17 | | -6f+4=40 | | -g=44 | | 9-x=3/5 | | -9p+3=21 | | -1.7(a+18)=-0.7(a+19) | | 0.7x=14x | | 4(x+3)+3x=3(x+4)+4x | | 9x^2+7x=-8 | | -d=75 | | 9/5-x=3 | | 9/5-x=4 | | 3y+1=2y+9 | | 6s=s+40 | | 25-x=87 | | 3=3x^2+8x | | y=kx^2-6x+3 | | 9/4x-1=26 | | 5x^2-7z-6=0 | | 5=-4x+4 | | w-1.3w+0.6=0.125(w+0.3) | | 5x=-4x+4 | | x^2-7x+17=7 | | -3y+1=-(3y-1) | | 4m+2=12m | | 4(x+2)=-3(7-4x)-8x | | y=(x+3)(x-8) | | -(-5v+6)=5v+30 | | 8x+3-2=8 |